Stereotypical Images in Dictionaries. The Image of the Prussians in the Example Sentences in the Słownik języka polskiego(1958–1969), edited by Witold Doroszewski - TESHAJEV SUNDERLAND, EVA (Glottodidactica, 2017)
Because dictionaries contain cultural references, they can provide insights into the stereotypical attitudes common in a nation towards other countries and ethnicities. This article investigates the image of the Prussians presented by the monolingual Polish dictionary ‘Słownik języka polskiego’ (1958–1969). The author explored this topic by examining all the headwords in this dictionary listed under the following letters: A, B, C, Ć, K, Z, Ź and Ż. She then analysed all the example sentences she found that mention Prussia or the Prussians. Though the author found only limited references to these topics, the example sentences that do deal with them display a negative attitude, which is in line with the general Polish attitudes held towards Prussia and the Prussians from the Partition times to the People’s Republic.